Do Islamic Rural Banks in West Java Become More Efficient Over Time? A Panel Stochastic Frontier Analysis - Mohamad Andri Ibrahim; Alya Naima Siti Najwa; Yayat Rahmat Hidayat; Panji Adam Agus Putra (KEUNIS, 2026)
Islamic Rural Banks (BPRS) play a crucial role in Indonesia’s Islamic microfinance sector, specifically in serving underbanked communities in rural areas. Therefore, understanding their efficiency dynamics is essential for ensuring long-term sustainability and assisting evidence-based policy formulation, particularly in the post-pandemic context where operational challenges intensify. This study investigates the efficiency dynamics of BPRS in West Java over the 2020–2023 period, decomposing efficiency into production and revenue components to identify specific sources of inefficiency. Using panel Stochastic Frontier Analysis (SFA) with 108 bank-year observations from 27 BPRS institutions, this study estimates both cost and profit efficiencies while controlling for environmental factors. The time-varying inefficiency model enables systematic assessments of temporal efficiency trends. The results reveal exceptionally high production efficiency (mean = 99.99%), indicating optimal input use. However, revenue efficiency shows substantial variation (mean = 72%) and a slight decline from 72.77% in 2020 to 71.6% in 2023. Contrary to the organisational learning theory, overall technical efficiency does not improve over time; instead, it decreases from 86.38% to 85.79%. This study provides the first evidence on BPRS temporal efficiency dynamics in the post-pandemic period and demonstrates that efficiency challenges stem primarily from revenue generation rather than operational weaknesses.